Overvaluation and earnings management - Chi, Jianxin (Daniel); Gupta, Manu (Journal of Banking & Finance, 2009)
Consistent with Jensen’s [Jensen, M., 2005. Agency costs of overvalued equity. Financial Management 34, 5–19] agency-costs-of-overvalued-equity prediction, we find that overvaluation is statistically and economically related to subsequent income-increasing earnings management. This relation is robust to a series of tests that address potential endogeneity concerns, including omitted variable bias and reverse causality. The agency costs of overvalued equity are substantial. Overvaluation-induced income-increasing earnings management is negatively related to future abnormal stock returns and operating performance, and this negative relation becomes more pronounced as prior overvaluation intensifies. Among the most overvalued firms, those with high discretionary accruals underperform those with low discretionary accruals during the following year by 11.88% as measured by the three-factor alphas, and by 12.87% points as measured by industry-adjusted unmanaged EBITDA-to-assets ratio.